Let's Get Engaged: The Nexus between Digital Technologies, Engagement and Learning - Sean Kearney; Julie Maakrun (MDPI AG, 2020)
The nexus between digital technologies, engagement and learning is often cited as being correlational, but is widely misunderstood. Research is clear that engagement can lead to better academic outcomes and improved learning, but less clear about the role of digital technologies in engaging students and the impact of digital technologies on student learning. Recent research suggests that in light of the increase in digital technologies in education that we must recognize the inherent challenges in increased use of digital technologies. In this article a small-scale case study was conducted to ascertain the level of student engagement and distraction during lectures. The study was repeated for two different cohorts of teacher education students to establish consistency of results. The authors sought to determine the level of academic engagement by having students record the number of digital distractions they encountered throughout the lecture. The students self-reported their distractions during a ~100 min lecture. The researchers found consistency between the two cohorts when looking at the number of self-reported distractions per student. The findings suggest that technology was a major distraction and further could be seen, due to the number of distractions, to be causing disengagement. In this article the authors use this case study to start a conversation about the possible perils of digital technologies with regard to engagement and learning and what this means in a future that may be dictated by technology-enhanced learning.